Józef Wittlin, Emil Cioran and the Experience of Exile - Szewczyk-Haake, Katarzyna (Porównania, 2025)
The article is devoted to Józef Wittlin’s essay Sorrow and Grandeur of Exile (English 1957, Polish 1959). It presents the history behind the creation of the text and, based on archival materials and letters, indicates how Wittlin’s approach to the problem of exile and exile literature evolved over several years. The analysis of the essay focuses on one of its important threads of thought – the dialogue with Emil Cioran’s Advantages of Exile (French 1952, Polish 1952). Wittlin’s reading of Cioran’s essay was an important moment for the crystallization of Wittlin’s position on the problem of emigration. The author concludes that both writers had in common the understanding of human existence as emigration (exile) and this metaphor plays an important role in their work. However, they interpret it differently from each other: Cioran in a pessimistic way, while Wittlin in religious categories.